Ivry Gitlis plays Tchaikovsky, Saint-Saëns, Bartók and Elgar - Tchaikovsky, Peter Ilich 1840-1893; Saint-Saëns, Camille 1835-1921; Bartók, Béla 1881-1945; Elgar, Edward 1857-1934 (Idéale Audience, 2007)
Astounding virtuosity, incomparable musicianship: Ivry Gitlis, the violin blessed by the Gods. "I need to play to feel alive. The day I stop, will mean I am dead." The youthful man who expresses himself in this way is Ivry Gitlis, who was born in Haïfa in 1922 and is fortunately still well alive! He plays, as he did in March 2008 at the Salle Pleyel with Martha Argerich. An adventurer, he always counted on his lucky star to feed him when he was broke: he left for New York by boat without a penny to take lessons with Professor Pashrus. On board he was invited every evening to dinner by a generous philanthropist who gave him a thousand dollars once he set foot in New York. Curious about everything and eager to experience new sensations, he played with the Rolling Stones, John Lennon, Eric Clapton and Dizzy Gillespie, among others. After a childhood in Israel, where his father worked as a miller, he studied at the Paris Conservatory where Bronislav Huberman had sent him.